The role of chicken eggs in modulating sarcopenic obesity and gut microbiota in db/db mice - Okamura, Takuro; Hasegawa, Yuka; Hamaguchi, Masahide; Sasano, Ryoichi; Fukui, Michiaki (Frontiers in Microbiology, 2023)
Background: Sarcopenia obesity, in which loss of muscle mass and fat accumulation occur simultaneously, is the pathological basis of type 2 diabetes mellitus. The usefulness of chicken eggs in sarcopenia prevention has been reported in several previous studies. The purpose of this study was to determine the beneficial effects of chicken eggs in the prevention of sarcopenic obesity in db/db mice. Methods: We raised 8-week-old db/db male mice, a model of sarcopenia obesity, for 8 weeks and fed them a diet mixed with dried whole eggs. The fecal microbiota transplant (FMT) group was treated with antibiotics for 2 weeks, starting at 6 weeks of age, followed by FMT twice a week until 16 weeks of age. Results: Eggs administered to db/db mice showed increased grip strength (p = 0.022) and muscle mass (p = 0.013), decreased visceral fat mass (p = 0.005), and significantly increased physical activity (p < 0.001). The FMT group of egg-fed mice showed a significant improvement in glucose intolerance and sarcopenic obesity. Sequencing of gene expression in the small intestine showed that the gene expression of amino acid transporters such as Slc6a18, Slc6a19, and Slc38a6 was increased in egg-fed mice. 16S rRNA sequencing of the gut microbiota showed an increase in the genus Vampirovibrio in both the egg-fed and FMT groups compared to that in egg-fed mice. Conclusion: The results of this study indicate that egg consumption not only increases the intake of amino acids and other nutrients but also alters the intestinal microbiota and increases amino acid absorption from the intestinal tract, suggesting that eggs might contribute to the ameliorative mechanism of sarcopenic obesity.